Tratamento de toletes de cana-de-açúcar para o controle da podridão-abacaxi em pulverização conjugada ao plantio mecanizado - Ferreira, Marcelo da C. [UNESP]; Werneck, Carolina F. [UNESP]; Furuhashi, Silvio; Leite, Gilson J. [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2008)
No plantio mecanizado da cana-de-açúcar, há dificuldades em se proteger a cultura contra pragas e doenças do solo, requerendo uma tecnologia de aplicação de produtos fitossanitários que respeite o ambiente e os custos de produção. O objetivo deste trabalho foi avaliar um sistema de pulverização para controle de doenças e pragas do solo, conjugado ao equipamento de plantio mecanizado de toletes de cana-de-açúcar, tomando como alvo-indicador a podridão-abacaxi. Delineou-se o experimento em blocos ao acaso, em área de plantio comercial da variedade SP-891115. A pulverização deu-se na região da calha do equipamento de plantio, por onde os toletes deslizam até o solo. Avaliaram-se o número de perfilhos brotados e a produção da cultura. Os resultados foram comparados pelo número e percentagem de perfilhos e pelo acréscimo na produção em relação à testemunha não-tratada. Com base nos resultados observados, concluiu-se que o sistema de pulverização de produtos fitossanitários conjugado ao plantio mecanizado proporcionou a recuperação da produtividade na cultura da cana-de-açúcar de até 15%, na maior dose utilizada para o controle da podridão-abacaxi, demonstrando ser promissor para o tratamento de toletes e visando à proteção contra doenças e pragas de solo.

On mechanized planting of sugarcane the stem there are harvested and buried in the furrow in successive operations. In this system there is difficultysome difficulties to protect the crop againstto pests and soil diseaseson the without enlarge the , requiring spray technology of pesticides that respect the environment and production costs and the environmental impacts, needing development on the spray technology by pesticides. Due that, is increasing the importance of problems like pineapple disease, that affect the meristematic arise and growing up of plants from soil. The aim of this research was evaluate a spraying system conjugated with mechanized planter, to treatment of stem on its way to the soil, for controlling of pineapple disease.. This research aimed to evaluate a spraying system to control both soil pests and diseases, conjugated with a mechanized planter of sugarcane stems, taking pineapple rottenness as an indicative target. The experiment was designed in randomized blocks on area of commercial plantingfield of sugarcane crop, variety SP-891115. The spraying was over a planter gutter, where the stem slidesstems slide down to the soil. That It was evaluated the number of arise and crop production. The results The results were compared to with the number and percentage of arises and percentage of production as over then check plot. We It was concluded that spraying system of pesticides conjugated with mechanized planter, provided satisfactory control of pineapple disease, with increasing at productivity recovery until on sugarcane crop up to 15%.%, on major dose applied to control of pineapple rottenness, revealing to be a promising system to stem treatment aiming to protect sugarcane crop from both soil pests and rottenness.
Treatment of sugarcane stem to control pineapple rottenness in conjugated spraying together with the mechanized planting
Keywords: Thielaviopsis paradoxa; tecnologia de aplicação; aplicação localizada; Thielaviopsis paradoxa; sprayingapplication technology; placed spray